Academician D.N. Pryanishnikov and the Russian National Research School of Agrochemistry - Yu. S. Tsench; I. S. Sidorov (Сельскохозяйственные машины и технологии, 2024)
The paper emphasizes the pivotal role played by Academician Dmitry Nikolaevich Pryanishnikov in the history of domestic agriculture development. His name is indelibly associated with the introduction of the agriculture chemicalization concept in 1924. Being a follower of such scientists as J.B. Boussingault, D.I. Mendeleev, and K.A. Timiryazev, Dmitry Nikolaevich Pryanishnikov not only proposed the chemicalization principle but also formed a comprehensive research program for its implementation. Moreover, he created necessary educational conditions for specialists and courageously defended his doctrine against the criticism of his opponents in the 1930-1950s. (Research purpose) The paper aims to analyze the scientific heritage and biography of Academician D.N. Pryanishnikov in the context of the domestic agriculture chemicalization. (Materials and methods) The analysis relies on scrutinizing scientific monographs, legal documents, and other publications utilizing biographical, chronological, genetic and typological methods of historical and scientific research. ( ) The findings show that Pryanishnikov’s significance in the history of science stems from both his personal research achievements and his foundational role in establishing the domestic tradition of agrochemistry. This influence was evident in his organizational and pedagogical performance. The study identifies two distinct generations of direct students and followers of this eminent agricultural chemist. (Conclusions) Academician D.N. Pryanishnikov elevated agrochemistry in our country to a systematic discipline, rightfully earning recognition as the founder of the national scientific school. Contemporary researchers, who maintain academic and ideological continuity with him, persist in advancing scientific eﬀorts to support the chemicalization of agriculture. In doing so, they make significant contributions to the nation’s food security and enhance fundamental knowledge about living organisms.